ADVANCE ORGANIZER AND BLENDED LEARNING AS A METHOD FOR IMPROVING THE PEDAGOGICAL COMPETENCE OF ARTS AND CULTURE TEACHERS IN INCLUSIVE SCHOOLS IN BANDUNG CITY - Haerani, Reni (International Journal of Education, 2024)
An important key in inclusive education is the pedagogical ability of teachers for all learners, including learners with disabilities. Teachers in carrying out their duties professionally not only have mastery of the substance of the material, but also need to be equipped with the ability to identify the characteristics of their students. This study aims to analyze and examine the pedagogical competence of teachers (dance) as a whole through the dimensions of scientific competence, psycho-pedagogical, and social competence. Given that inclusive education has high complexity, so the results of observations need to be followed up, because there are many obstacles faced by teachers (dance), especially in terms of modifying and accommodating the curriculum, besides that teachers have not been able to provide learning services according to the various characteristics of students (inclusive). So it is necessary to conduct a study of improving pedagogical competence through recognition training through an Advand organizer-based approach with a blended learning strategy. This mixed method research qualitative data begins with field studies or observations and interviews, researchers see and pay attention to the pedagogical competence of teachers, the conditions of children with disabilities, and dance learning. The main quantitative data is the pedagogical competence of dance teachers obtained through test instruments and questionnaires after the end of the training. The research sample was carried out on six teachers in public junior high schools organizing inclusive education in Bandung City. The results of the training showed an increase in the pedagogical competence of dance teachers in the aspects of scientific, psychopedagogical and social competence for the better. Another impact of the results of teacher recognition is able to encourage students to increase their willingness to learn, especially for disabilities (slow learners), be more open and able to implement contextual learning and increase the social interaction of students, especially disabilities (slow learners) through positive interventions.